Transcriptomics–metabolomics joint analysis: New highlight into the triterpenoid saponin biosynthesis in quinoa (Chenopodium quinoa Willd.) - Zhao, Yulu; Ma, Yucong; Li, Jiawei; Liu, Bin; Liu, Xiaoqing; Zhang, Jianheng; Zhang, Min; Wang, Chunmei; Zhang, Liping; Lv, Wei; Mu, Guojun (Frontiers in Plant Science, 2022)
Quinoa (Chenopodium quinoa Willd.) contains various physiologically active substances, including vitamins, polyphenols, flavonoids, phytosterols, and saponins. Research showed that saponins were the protective substances in the outer layer of quinoa seeds to defend against microbes, herbivores, and insects. Because the aglycones of quinoa saponins are triterpenoids, they are called triterpenoid saponins (TSs). In addition, the presence of TS imparted bitterness in quinoa and resulted in anticancer and anti-inflammatory effects. In this study, the seeds of low-saponin quinoa, NT376-2 (N), and high-saponin quinoa, B-12071(B), at 30 and 60 days after flowering (DAF) were used to measure the TS content and evaluated for their transcriptomic and metabolomic profiles. The amounts of TS were found to significantly differ between all possible comparisons: N and B at 30 DAF (N1_vs_B1), N and B at 60 DAF (N2_vs_B2), N at 30 DAF and 60 DAF (N1_vs_N2), and B at 30 DAF and 60 DAF (B1_vs_B2). RNA sequencing (RNA-seq) was used to screen differentially expressed genes (DEGs) and revealed 14,703 upregulated DEGs and 26,267 downregulated DEGs in the four comparison groups. The 311 overlapping DEGs found in the four comparisons were used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses to screen for DEGs related to TS biosynthesis in quinoa. Metabolomics analysis identified acetyl-CoA, 1-hydroxy-2-methyl-2-butenyl-4-diphosphate, farnesal, and (S)-2,3-epoxysqualene as the key differentially accumulated metabolites (DAMs). Transcriptomics–metabolomics joint analysis showed that triterpenoid biosynthesis and terpenoid backbone biosynthesis were the enriched pathways of TS biosynthesis; farnesal were the key DAMs shared in the four comparison groups and associated with 10 key candidate DEGs related to TS biosynthesis in quinoa. These results provided important references for in-depth research on the metabolic mechanism of TS in quinoa.